Coping power program - Lochman, John E. (Oxford University Press, 2008)
This program is an evidence-based intervention for behavioral in pre-adolescent children (grades 5 and 6). Continuing the work of the Fast Track Program, currently under contract, this intervention targets children who are beginning to show signs of severe aggression and social dysfunction at school. Children who begin to exhibit aggression as pre-adolescents are much more likely to have histories of substance abuse, interpersonal violence, and criminal behavior in their adolescence. By targeting these children before their behavior has become extremely dangerous or unmanageable, this program has been proven to reduce the occurence of these programs, and to improve functioning in school